Factors affecting the adoption of mobile services - Kargın, Banu. (Thesis (M.A.)-Bogazici University. Institute for Graduate Studies in the Social Sciences, 2007., 2007)
Mobile technologies are gaining more popularity and diffusing into every aspect of our life. Value Added Services (VAS) has a huge impact on consumers’ usage patterns and has become a significant differentiator across the operators. These led to new opportunities in innovation of differentiating services. Better services will be best developed by understanding the requirements of the users. In this study, our intention is to shed some light on the process of mobile service adoption by investigating value added services especially for informative services. The study started with background research to identify factors determining the adoption of mobile services; then continued with qualitative studies; namely interviews, brainstorming sessions, and expert focus group. After these studies, an experimental study was conducted. During this experimental study, a conjoint analysis had been conducted. During conjoint analysis, product preference factors were explored. Service cost and service speed were seen as critical factors. In addition to these, according to results of regression analyses which are done to find the determinants of mobile service intention, attitude and usefulness were found to be significant factors parallel to literature. Personalization, mobility, user experience and content were identified as indirect determinants of attitude mediated through usefulness.
Keywords: Value-added networks (Computer networks); Mobile communication systems.